STUDIES IN CYPERACEAE. VII. NEW EVIDENCES FOR THE REVALIDATION OF FIMBRISTYLIS VELATA - E Govindarajalu (Research Center for Biology, 1974)
Anatomical and palynological evidences are advanced in addition to the morphological characters for the revalidation of Fimbristylis velata R. Br., which often has been recognized only as varieties of F. squarrosa Vahl or other species. A full description of this taxon is presented.